2000
DOI: 10.1017/s0142716400003064
|View full text |Cite
|
Sign up to set email alerts
|

Grammaticality judgments in a second language: Influences of age of acquisition and native language

Abstract: Native Spanish early and late acquirers of English as well as native Vietnamese early and child acquirers of English made grammaticality judgments of sentences in their second language. Native Spanish early acquirers were not distinguishable from native English speakers, whereas native Spanish late acquirers had difficulty with all aspects of the grammar tested except word order. Native Vietnamese early acquirers had difficulty with those aspects of English that differ markedly from Vietnamese. Native Vietname… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
155
1
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(178 citation statements)
references
References 23 publications
18
155
1
4
Order By: Relevance
“…This point is quite relevant in tasks that include a delayed response as the response is moved outside the realm of languagespecific processing. Lastly, some authors have argued that the grammaticality judgment task may not be a good measure of L2 linguistic knowledge (McDonald, 2000) or may over-/ underestimate L2 syntactic knowledge (Juffs, 2004). In particular, McDonald (2000) pointed out that variables such as syntactic rule types or interpretation of ungrammatical constructions may alter the results of a grammaticality judgment task and renders the task unreliable.…”
Section: Offline Versus Online Behavioural Resultsmentioning
confidence: 99%
“…This point is quite relevant in tasks that include a delayed response as the response is moved outside the realm of languagespecific processing. Lastly, some authors have argued that the grammaticality judgment task may not be a good measure of L2 linguistic knowledge (McDonald, 2000) or may over-/ underestimate L2 syntactic knowledge (Juffs, 2004). In particular, McDonald (2000) pointed out that variables such as syntactic rule types or interpretation of ungrammatical constructions may alter the results of a grammaticality judgment task and renders the task unreliable.…”
Section: Offline Versus Online Behavioural Resultsmentioning
confidence: 99%
“…According to Flege (2002), even though individuals are exposed to an L2, in an L2 environment, young children often end up speaking the L2 with a non-native accent. The above-mentioned notion was well backed by a study by McDonald (2000), in which it was found that early exposure of English from a Spanish-speaking background had clear advantages on the grammatical judgment test and were able to perform to native levels.…”
Section: International Journal Of English Linguisticsmentioning
confidence: 90%
“…Son yıllarda hız kazanan beyindilbilimi ve psikodilbilim çalışmaları iki dili beyinde bilgi işlemleme olarak ele alarak bu olgunun açıklanmasında önemli veriler sağlamıştır (McDonald, 2000;Hahne, 2001;Wartenburger vd., 2003;Felser ve Roberts, 2007;Jiang, 2007;Weber ve Lavric, 2008;Saur vd., 2009;Guo vd., 2009;Mergen, 2010). Ancak dilin dilbilgisi, sesbilgisi, sözcükbilgisi gibi özellikleri açısından olduğu kadar duygusal içeriği açısından da ele alınması bu çalışmalara ayrı bir bakış açısı sağlamıştır.…”
Section: International Journal Of Languages' Education and Teachingunclassified
“…Beyindilbilimi ve psikodilbilim alanında yapılan çalışmalara bakıldığında, anadilinin ediniminden sonra formal olarak öğrenilen dilin anadili konuşucularından farklı işlemlendiği görülmektedir (McDonald, 2000;Hahne, 2001;Wartenburger vd., 2003;Felser ve Roberts, 2007;Jiang, 2007;Weber ve Lavric, 2008;Saur vd., 2009;Guo vd., 2009;Mergen, 2010). İkinci dilini anadilinden sonra ve formal eğitimle öğrenen bireylerde duygu içerikli dilin algılanması ve üretimi yukarıda sözü edilen farklılıklardan nasıl etkilenmektedir ?…”
Section: International Journal Of Languages' Education and Teachingunclassified